ALTERNATIVE URBAN REGENERATION POLICIES OF BROWN FIELDS LIKE OLD MILITARY CAMPS FOR THE CITY OF ALEXANDROUPOLIS - Costas Portokalidis; Foteini Zygouri (European Regional Science Association (ERSA), 2011)
It is generally accepted that the lack of free public spaces in Greek cities, is one of the most severe urban planning problems, not only in the central urban areas but also in the peripheral neighbourhoods. Furthermore, it is a fact that through the land use legal framework there have been efforts towards the implementation of a number of planning tools, regulations, thresholds, methods etc in order to obtain and secure an appropriate level of acceptable urban public space mainly for parks, playgrounds and squares, which would ensure at least a minimal level of essential (sustainable) free urban public space. The reality has shown that this effort has not been successful until today. The provision, the quality and the spatial distribution of public space in Greek cities, cannot correspond to the continuously increasing needs and wishes of citizens. This is probably the most serious weakness of the Greek urban planning system, because it cannot achieve the objectives of urban sustainability. In this manner and specifically for some cities, military camps that exist and occupy vital space in the urban tissue, present a new challenge for "liberating" this space and providing new quality to the urban environment. The present paper presents a case study in which, proposals are formulated for the transformation of "brown" space occupied by military camps, to urban free space, useful for the adjacent neighbourhoods, as well as for the city of Alexandroupolis in general. The importance of the proposal also lies in the fact that this transformation will take in account the present rigid and complex legal and institutional framework, having, thus, the elements of a pilot intervention. The basic approach is based on the principle that military camps are public land, and can be used in the formulation of a regeneration policy. Critical elements of the approach are the assessment of benefit that the transformation of this space will bring to the city, the allocation of the benefits to the neighbourhoods, the effectiveness of spatial integration of the new space in the existing urban structure, and the absolute protection of public space in the whole city.
Keywords: 330